Geographic variation and taxonomy of red-tailed Gymnophthalmus (Squamata: Gymnophthalmidae) from Amazonian Savannas - Recoder, Renato Sousa; Vechio, Francisco Dal; Marques-Souza, Sergio; Teixeira, Mauro Jr.; Silva-Da-Silva, Maiume; Santos-Jr., Alfredo P.; Ribeiro, Síria; Barrio-Amorós, Cesar; Rodrigues, Miguel Trefaut (Zootaxa, 2018)
Gymnophthalmus represents a challenging group for systematics of microteiid lizards. Due to scarcity of exemplars and molecular data, the taxonomy of the genus has been unstable, and six of its eight species are considered part of a poorly-delimited complex of unisexual and bisexual species. Unnamed populations of red-tailed Gymnophthalmus from savanna enclaves in Amazon, similar to G. vanzoi but with differences in color pattern, have been noted in the literature. Here, we used molecular and morphological data to test the taxonomic status of the Central Amazonian red-tailed Gymnophthalmus (G. sp.). Our molecular analysis recovered a close relationship between G. vanzoi and G. sp. from Central Amazon, with minimal divergence. Samples were similar in scale counts but presented significant variation in color pattern and morphometry. Despite the geographic isolation, individuals of both populations cannot be fully differentiated based on morphology. Thus, our results suggest that G. vanzoi has a wider distribution, including the Central Amazonian red-tailed Gymnophthalmus and likely morphologically similar populations from other enclaves of Amazonian savannas, which may have been isolated recently. Based on our comparative analysis, we highlight some characters proved useful for differentiating Brazilian Gymnophthalmus and discuss some prospects for the taxonomy of the genus.